A comparative assessment of water quality of two reservoirs in an ephemeral river in the desert climate of Namibia: Measures to control, and factors affecting growth of toxic cyanobacteria - Sirunda, Jaime Johannes (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.